The potential application of human PIG‐A assay on azathioprine‐treated inflammatory bowel disease patients. (6th December 2019) - Cao, Yiyi; Wang, Xiaolei; Liu, Weiying; Feng, Nannan; Xi, Jing; You, Xinyue; Chen, Ruixue; Zhang, XinYu; Liu, Zhanju; Luan, Yang
Abstract : The rodent Pig‐a assay has been used extensively as a potential regulatory assay for evaluating the in vivo mutagenicity of test substances. Although the assay can be conducted in different mammalian species, there have been only a few reports describing its use in humans, and rarely in genotoxicant‐exposed human populations. In this study, PIG‐A mutation frequencies (MFs) were evaluated in 36 azathioprine (AZA; human carcinogen)‐treated inflammatory bowel disease (IBD) patients and 36 healthy volunteers. IBD patients exhibited a slight but statistically higher MF (6.10 ± 4.44 × 10 −6 ) than healthy volunteers (4.97 ± 2.74 × 10 −6 ) ( P = 0.0489). The estimated relative risk for the exposed patients was 1.22 which indicated that AZA is a risk factor for inducing PIG‐A mutation. However, the PIG‐A MF showed no associations with AZA treatment duration or total AZA exposure. In addition, we performed the cytokinesis‐block micronucleus test on the same samples. The frequencies of micronuclei (MN) and nuclear buds (NBUD) in IBD patients (MN: 4.70 ± 2.86‰; NBUD: 1.89 ± 0.95‰) were significantly higher than in healthy volunteers (MN: 1.47 ± 0.77‰, P < 0.001; NBUD: 0.90 ± 0.58‰, P = 0.004). MN frequency also had significant correlations with AZA treatment duration ( P = 0.011) and total AZA exposure ( P = 0.018). Our findings indicate that AZA‐treated IBD patients have only a marginally significant increase in PIG‐A MF; in contrast, a much stronger AZA‐associated increase in genotoxicity was detected with the lymphocyte MN assay. Environ. Mol. Mutagen. 2019. © 2019 Wiley Periodicals, Inc.